Anchoring ligand engineering enables highly stable MA-free perovskite solar cells with a minimal VOC deficit of 0.32 V - Li, Chaohui; Vincze, Andrej; Park, Hyoungwon; Streller, Fabian; Götz, Klaus; Qiu, Shudi; Byun, Jiwon; Shang, Ying; Yuan, Zhangyu; Dong, Lirong; Tian, Jingjing; Peng, Zijian; et al. (Energy and Environmental Science, 2025)
Ligand engineering is an effective method to reduce defects in perovskite solar cells (PSCs) and to enhance efficiency. Likewise, enhancing device stability through ligand engineering is currently emerging as a key focus to suppress the bidirectional migration of halides and silver ions, which otherwise can cause irreversible chemical corrosion to the electrode and perovskite layer. Here, triphenylphosphine oxide (TPPO) is demonstrated to improve the long-term operational stability of PSCs when introduced at the interface between the perovskite and the electron transport layer (ETL). TPPO effectively eliminates uncoordinated Pb2+ and thus reduces surface defects. Accordingly, the target solar cell yields a hero power conversion efficiency (PCE) of 26.01% and a maximum open-circuit voltage (VOC) of 1.23 V, representing the minimum voltage deficit (0.32 V) reported for methylammonium-free (MA-free) PSCs. Moreover, long-term operational analysis reveals that the bidirectional migration of halides and silver ions is significantly suppressed, resulting in enhanced device stability. TPPO-modified PSCs retain 90% of the initial PCE after 1200 hours of operation in maximum power point tracking. Ligand engineering with TPPO marks a significant advancement in enhancing the stability of PSCs and is fully compatible to upscaling scenarios.
CRIS-Team Scopus Importer:2025-07-18

Overcoming optical losses in thin metal-based recombination layers for efficient n-i-p perovskite-organic tandem solar cells - Tian, Jingjing; Liu, Chao; Forberich, Karen; Barabash, Anastasia; Xie, Zhiqiang; Qiu, Shudi; Byun, Jiwon; Peng, Zijian; Zhang, Kaicheng; Du, Tian; Sathasivam, Sanjayan; Macdonald, Thomas J.; et al. (Nature Communications, 2025)
Perovskite-organic tandem solar cells (P-O-TSCs) hold substantial potential to surpass the theoretical efficiency limits of single-junction solar cells. However, their performance is hampered by non-ideal interconnection layers (ICLs). Especially in n-i-p configurations, the incorporation of metal nanoparticles negatively introduces serious parasitic absorption, which alleviates photon utilization in organic rear cell and decisively constrains the maximum photocurrent matching with front cell. Here, we demonstrate an efficient strategy to mitigate optical losses in Au-embedded ICLs by tailoring the shape and size distribution of Au nanoparticles via manipulating the underlying surface property. Achieving fewer, smaller, and more uniformly spherical Au nanoparticles significantly minimizes localized surface plasmon resonance absorption, while maintaining efficient electron-hole recombination within ICLs. Consequently, optimized P-O-TSCs combining CsPbI2Br with various organic cells benefit from a substantial current gain of >1.5 mA/cm2 in organic rear cells, achieving a champion efficiency of 25.34%. Meanwhile, optimized ICLs contribute to improved long-term device stability.
CRIS-Team Scopus Importer:2025-01-31

Overcoming size limits with dynamic templates enabling large area single crystal nanowire arrays for photodetectors - Feng, Mingjie; Byun, Jiwon; Li, Zongbao; Xie, Zhiqiang; Lu, Wenbo; Wen, Xin; Ding, Liang; Wu, Tingting; Jamshaid, Sumbal; Götz, Klaus; Li, Chaohui; Peng, Zijian; et al. (Nature Communications, 2025)
Ordered one dimensional perovskite single-crystal nanowire arrays, which combine high surface-to-volume ratios, directional charge transport, and mechanical flexibility, are typically prepared through solution or vapor phase techniques using templates of silicon, polydimethylsiloxane, photoresist, or aluminum oxide to control crystal growth. However, the size limits of these templates restrict the scalability of the arrays. Here, we introduce a dynamic template-assisted coating strategy that integrates blade coating to address this limitation. The method enables deposition of nanowire arrays on substrates with an area 12 times larger than the template. Incorporating a fluorinated passivating agent into the precursor suppresses surface defect formation and improves structural quality. Photodetectors based on MAPbBr3 arrays achieve a detectivity of 3.9 × 1014 Jones, a linear dynamic range of 160.3 dB, and a responsivity of 1660 A W-1, and retain 90.3% of their photocurrent after 300 h at 85% relative humidity without encapsulation.
CRIS-Team Scopus Importer:2025-11-21

Tailoring the Dimensionality of 2D/3D Heterojunctions for Inverted Perovskite Solar Cells - Li, Chaohui; Zhang, Kaicheng; Maiti, Santanu; Peng, Zijian; Tian, Jingjing; Park, Hyoungwon; Byun, Jiwon; Xie, Zhiqiang; Dong, Lirong; Qiu, Shudi; Bornschlegl, Andreas; Liu, Chao; et al. (ACS Energy Letters, 2024)
Interface engineering is crucial to achieving stable perovskite photovoltaic devices. A versatile approach is developed to tailor interface properties via integrating co-assembled monolayers (co-SAMs) at the p-type buried interface and by capping a two-dimensional (2D) perovskite layer at the n-type upper interface with vacuum quenching. Optimized co-SAMs promote the coverage of the hole transport layer, significantly reducing the incidence of leakage currents. Based on this foundation, we develop damp-heat-stable perovskite solar cells by precisely tailoring the fragments of 2D perovskite layers through vacuum annealing with phenethylammonium iodide. An impressive open-circuit voltage of 1.216 V is achieved, corresponding to 92% of the value determined by the detailed-balance limit, along with a power conversion efficiency of 23.68%. Ultimately, integrating co-SAMs and the vacuum-assisted annealing fabricated devices maintain 96% and 80% of initial efficiencies after 1200 and 500 h of tracking at a maximum power point under 55 and 85 °C, respectively.
CRIS-Team Scopus Importer:2024-02-23